Neptune or poseidon: Implementing EU and global maritime safety law in national agency - Gulbrandsen, Christer (2013)
Arguably, the EU represents a qualitatively different international order from traditional intergovernmental international organizations (IOs), as it has accumulated functions and capacities beyond these. This article compares how the EU and the International Maritime Organization impact three aspects of a national agencys implementation of international rules: application, conflicts over policy agendas and how it deals with non-compliance. Interviews reveal the EU and the IMO as more similar than expected, but still different. Whereas application seems impacted by various supporting functions of both IOs, the EU's heavy enforcement mechanisms may possibly hamper the detection of non-compliance and its indepen dent agenda-setting powers may create animosity among national officials over the content of EU rules. - Reproduced.
Keywords: Law of sea